If nth term of an A.P. is (2n+1), what is the sum of its first three terms?
A1111:
Sum of 'n' odd terms = n²
Answers
Answered by
7
Hey here is your answer
Attachments:
![](https://hi-static.z-dn.net/files/dec/0d7ed23ee0f43ca795bb682d6a9ec74f.jpg)
![](https://hi-static.z-dn.net/files/da2/b93ae27eb783a28778e61bb62fb475fd.jpg)
Answered by
2
We have :-
=> General term = 2n + 1
First term => n = 1 => 2(1) + 1 = 3
Sum of n terms =
![= > \frac{n}{2} (3 + 2n + 1) = n(n + 2) = > \frac{n}{2} (3 + 2n + 1) = n(n + 2)](https://tex.z-dn.net/?f=+%3D+%26gt%3B+%5Cfrac%7Bn%7D%7B2%7D+%283+%2B+2n+%2B+1%29+%3D+n%28n+%2B+2%29)
Now, sum of first three terms => n = 3
=> n(n + 2) = 3(3 + 2) = 3 × 5 = 15
Hope it'll help you.....
=> General term = 2n + 1
First term => n = 1 => 2(1) + 1 = 3
Sum of n terms =
Now, sum of first three terms => n = 3
=> n(n + 2) = 3(3 + 2) = 3 × 5 = 15
Hope it'll help you.....
Similar questions